POSTRIZATION system to reduce metal levels and increase the pH of pit water active tin mining - Desti Ritdamaya; Moh. Irma Sukarelawan; Jessica Jessica; Lince Lince; Velysya Velysya (Universitas Ahmad Dahlan, 2022)
The pits left by unconventional tin miners in Bangka Belitung have formed a kind of water reservoir usually used for consumption when there is a drought or scarcity of clean water. This pit water has been contaminated with heavy metals and has a low pH, making it unfit for consumption. Therefore, this study aims to test the POSTRIZATION system that has been developed to increase pH and reduce heavy metal levels so that the water quality becomes fit for consumption. Increasing the pH and decreasing the metal content is carried out through 3 stages: composting, filtration, and distillation. The water sample came from one of the active mining pits in Baturusa, Bangka Regency. The pH level and metal content were measured before and after treatment. The pH level of the water was measured using a pH meter, and the metal content was measured using an Atomic Absorption Spectrometer (AAS). Changes in pH and metal content were calculated using the percentage technique. The POSTRIZATION results showed that the pH of the water increased to 7.6, and the metal content decreased by more than 93%. So, the POSTRIZATION system effectively restores the quality of pit water to fit for consumption. This, directly or indirectly, can prevent people from getting various diseases due to consuming water contaminated with heavy metals.